Thermodynamic and structural profiles of multi‐target binding of vinblastine in solution. Issue 12 (17th September 2022) - Gopi, Priyanka; Singh, Shweta; Islam, Md Maidul; Yadav, Akankasha; Gupta, Neelima; Pandya, Prateek
Abstract: Structural information about drug‐receptor interactions is paramount in drug discovery and subsequent optimization processes. Drugs can bind to multiple potential targets as they contain common chemical entities in their structures. Understanding the details of such interactions offer possibilities for repurposing and developing potent inhibitors of disease pathways. Vinblastine (VLB) is a potent anticancer molecule showing multiple receptor interactions with different affinities and degrees of structural perturbations. We have investigated the multi‐target binding profile of VLB with DNA and human serum albumin (HSA) in a dynamic physiological environment using spectroscopic, molecular dynamics simulations, and quantum mechanical calculations to evaluate the structural features, mode, ligand and receptor flexibility, and energetics of complexation. These results confirm that VLB prefers to bind in the major groove of DNA with some inclination toward Thymidine residue and the TR‐5 binding site in HSA with its catharanthine half making important contacts with both the receptors. Spectroscopic investigation at multiple temperatures has also proved that VLB binding is entropy driven indicating the major groove and TR‐5 binding site of interaction. Finally, the overall binding is facilitated by van der Waals contacts and a few conventional H‐bonds. VLB portrays reasonable conformational diversity on binding with multiple receptors. Abstract : Schematic representation of Vinblastine interactions with DNA duplex using spectroscopic and in‐silico methods.